Potensi Ekstrak Etanol Daun Afrika (Vernonia amygdalina Del.) terhadap Perbaikan Kerusakan Ginjal Tikus Putih (Rattus norvegicus) yang Diberikan Sopi - Petra Willem Rodnels Melatunan; Chomsa Dintasari Umi Baszary; Meillisa Carlen Mainassy (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Excessive consumption of sopi in the long term can cause various chronic diseases such as kidney failure. This study aims to determine the potential of African leaf ethanol extract in repairing sopi-induced kidney damage in white rats. The experimental design used was a completely randomized design (CRD) with five treatments. The sample was 18 mice. Groups of mice K (-), K (+), P1, P2 and P3 were induced with 1.28 ml of sopi/animal. K (+) mice were given Furosemide as a comparison. Groups P1, P2 and P3 were given ethanol extract of African leaves at doses of 1.28, 2.56 and 5.12 ml/head/day respectively. The results obtained were analyzed using analysis of variance (ANOVA) then followed by the Tukey HSD post hoc test. The results of the study showed that there was an effect of reducing creatinine levels and improving kidney damage in white mice due to administration of African leaf ethanol extract, where the effective dose was 2.56ml/head/day. So it can be concluded that the ethanol extract of African leaves at a dose of 2.56 ml/head/day has the potential to reduce creatinine levels and repair sopi-induced kidney damage in white rats, the results of which are also the same as those shown by the drug Furosemide. However, giving higher doses will be toxic to the body.